2016
DOI: 10.3389/fpls.2016.00594
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Competition and Allelopathy on the Trade-Off between Plant Defense and Growth in Two Contrasting Tree Species

Abstract: In contrast to plant-animal interactions, the conceptual framework regarding the impact of secondary metabolites in mediating plant-plant interference is currently less well defined. Here, we address hypotheses about the role of chemically-mediated plant-plant interference (i.e., allelopathy) as a driver of Mediterranean forest dynamics. Growth and defense abilities of a pioneer (Pinus halepensis) and a late-successional (Quercus pubescens) Mediterranean forest species were evaluated under three different plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 80 publications
(87 reference statements)
2
72
1
Order By: Relevance
“…The role of hydroxyacetophenones in defence may influence the conservation of its biosynthetic pathway across the Pinaceae. Hydroxyacetophenones can reduce insect herbivory or fungal growth in Picea and Larix (Delvas et al, ; Münzenberger et al, ; Münzenberger, Heilemann, Strack, Kottke, & Oberwinkler, ; Parent et al, ; Strunz et al, ) and have been reported to have allelopathic effects (Fernandez et al, ; Ruan et al, ). In P. glauca , the foliar accumulation of piceol and pungenol from late June is synchronized with the development of the most damaging stage of spruce budworm and is linked with resistance (Parent et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of hydroxyacetophenones in defence may influence the conservation of its biosynthetic pathway across the Pinaceae. Hydroxyacetophenones can reduce insect herbivory or fungal growth in Picea and Larix (Delvas et al, ; Münzenberger et al, ; Münzenberger, Heilemann, Strack, Kottke, & Oberwinkler, ; Parent et al, ; Strunz et al, ) and have been reported to have allelopathic effects (Fernandez et al, ; Ruan et al, ). In P. glauca , the foliar accumulation of piceol and pungenol from late June is synchronized with the development of the most damaging stage of spruce budworm and is linked with resistance (Parent et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyacetophenones can reduce insect herbivory or fungal growth in Picea and Larix (Delvas et al, 2011;Münzenberger et al, 1995;Münzenberger, Heilemann, Strack, Kottke, & Oberwinkler, 1990;Parent et al, 2017;Strunz et al, 1986) and have been reported to have allelopathic effects (Fernandez et al, 2016;Ruan et al, 2011). In Table S2).…”
Section: Broadly Conserved Biosynthetic Model Across the Pinaceaementioning
confidence: 99%
“…Allelopathy can occur as part of interference responses between plants [23], though allelopathy is generally considered to be less important in plant interference than competition [24]. Wardle [25] has reviewed the allelopathic potential of weeds in the New Zealand pasture ecosystem and found that some of these species release chemicals into their surrounding environment, potentially causing detrimental effects on the production of desirable pasture species [26].…”
Section: Allelopathic Plantsmentioning
confidence: 99%
“…Similarly, phenolics released by plants may also play a key role in influencing the soil microbial community structure [19] and litter decomposition process [20]. For instance, autotoxicity of canopy trees on their own seedlings probably plays a role in forest species turnover along succession in Mediterranean forests [5]. Some autotoxic compounds released by asparagus (Asparagus officinalis) probably inhibit its own growth and can also be a reason for "asparagus decline" [21].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Autotoxicity refers to the phenomenon in which plants release their metabolites into the surrounding environment by volatilization, rainwater leaching, decomposition, and root excretion [4]; these metabolites then inhibit seed germination or other individuals' or their own seedlings' growth directly or indirectly. Canopy trees' autotoxicity to their seedlings may play an important role in forest species replacement [5], and the existence of autotoxicity was proved in many natural populations [4,6]. Current studies on plant autotoxicity have shown that allelochemicals mainly inhibit plant growth in the following ways: (1) Plant growth is directly inhibited by affecting photosynthesis and altering plant cell membrane structures and plant defense systems [7,8].…”
Section: Introductionmentioning
confidence: 99%